The nightmare before Christmas - Burton, Tim, 1958- (New York : Disney Press, 1993)
The king of Halloween decides he wants a new holiday, and Christmas will never be the same.
Booklist
Library Talk
New York Times
4.2
3-6.
3-6
Keywords: Halloween -- Fiction; Stories in rhyme; Christmas -- Fiction; Halloween -- Fiction; Stories in rhyme